Metode Alternatif Penyimpanan Udang Segar dengan Nisin dari Lactococcus lactis sebagai Pengawet Alami - Dyah Fitri Kusharyati; P Maria Hendrati (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
Nisin is a Lactococus lactis metabolite, one of natural preservatives against microbes. The antimicrobial inhibition is influenced by its concentration and contact time with the targeted microbes. The aim of the study was to know the concentration of L. lactis extract and optimal time of soaking the growing shrimp bacterial in refrigerator temperature for nine days. This study was conducted experimentally applying factorial design. The first factor was soaking duration, i.e. 0 minute (P0), 30 minutes (P1), 60 minutes (P2), and 90 minutes (P3), while the second factor was concentration levels of metabolite of L. lactis extract. The results showed that the metabolite has an inhibitory effect on shrimp bacterioal in dosed dependent way. The best performance of inhibition was detected at 60 minute-soaking duration.